2015
DOI: 10.1371/journal.pone.0121996
|View full text |Cite
|
Sign up to set email alerts
|

Has introduction of rapid drug susceptibility testing at diagnosis impacted treatment outcomes among previously treated tuberculosis patients in Gujarat, India?

Abstract: BackgroundRevised National TB Control Programme (RNTCP) in India recommends that all previously-treated TB (PT) patients are offered drug susceptibility testing (DST) at diagnosis, using rapid diagnostics and screened out for rifampicin resistance before being treated with standardized, eight-month, retreatment regimen. This is intended to improve the early diagnosis of rifampicin resistance and its appropriate management and improve the treatment outcomes among the rest of the patients. In this state-wide stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
0
10
1
Order By: Relevance
“…We noticed that patients who were recorded as “lost to follow-up” are no longer at higher risk of defaulting during their retreatment [ 6 , 7 ]. The treatment success is also higher than that observed elsewhere [ 13 ]. Furthermore, of the different types of retreatment TB patients, the highest success rate was reported in those who relapsed.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…We noticed that patients who were recorded as “lost to follow-up” are no longer at higher risk of defaulting during their retreatment [ 6 , 7 ]. The treatment success is also higher than that observed elsewhere [ 13 ]. Furthermore, of the different types of retreatment TB patients, the highest success rate was reported in those who relapsed.…”
Section: Discussioncontrasting
confidence: 64%
“…MDR-TB patients can promptly start appropriate treatment without having to start and fail a retreatment regimen, which has individual benefits as well as preventing further transmission of drug-resistant TB in the community. Studies from India have also shown that this approach improves treatment outcomes among previously treated patients [ 13 ]. According to our study findings, one-quarter of the patients did not achieve this goal of DST.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore MSF is planning to do a clinical trial in collaboration with national health authorities to generate further robust evidence for best treatment options for HIV-VL co-infected patients in India.’ Kyaw N. et al (2015), Myanmar [30]The study used routinely collected programme data on all patients aged ≥ 15 years starting first-line tenofovir-based ART between 2012 and 2013. Creatinine clearance was assessed at base line and 6 monthly and incidence of renal dysfunction was calculated.The low incidence of renal toxicity in the patient cohort suggests that routine assessment of creatinine clearance may not be needed and could be targeted to high risk groups if resources permit. ‘ The national program adopted the alternative low cost screening method (urine protein testing) for screening of renal dysfunction in patients taking tenofovir and now uses the creatinine test only in high risk patients.’ Contributed to existing evidence leading to scale up of interventions Dave P. et al (2015), India [31]This was a retrospective cohort study involving a review of electronic patient records maintained routinely under the National Tuberculosis Programme, Gujarat, India in 2013.Offering rapid drug susceptibility testing (DST) at diagnosis improved the treatment outcomes among patients with pulmonary tuberculosis. ‘ The study findings strengthened the evidence of the effect of rapid DST at diagnosis on treatment outcomes of TB patients, which reinforced the national policy and has contributed to scale up of rapid DST facilities in the country.’ Change in policy and/or practice at subnational level Shewade H. et al (2014), India [32]Mixed-methods study, quantitative component consisted of retrospective cohort study reviewing records of all presumptive MDR-TB patients between October 2012 and September 2013. The qualitative component included in-depth interviews with key informants involved in programmatic management of drug-resistant tuberculosis services.High pre-diagnostic and pre-treatment attrition with 46% and 29%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Reasons for PTLFU in adults with drug-susceptible TB Patient-, family, or society-related reasons for PTLFU among drug-susceptible TB patients included financial and job constraints preventing patients from returning to health facilities to start therapy [68,76] ( Fig 11). Patient mobility was a barrier across multiple studies [67,68,77],…”
Section: Factors Associated With Non-completion Of Sputum Microscopy ...mentioning
confidence: 99%
“…with nearly one-third of patients in 1 study experiencing PTLFU due to temporary job-related migration [68]. Psychological reasons were common, with 5% to 25% of patients across multiple studies citing concerns about TB stigma, disbelief in their diagnosis, or treatment refusal as contributing to PTLFU [44,67,72,76,77]. Death before treatment initiation affected 4% to 40% of patients across multiple studies [64,67,72,74,77].…”
Section: Factors Associated With Non-completion Of Sputum Microscopy ...mentioning
confidence: 99%